Application of Flipped Classroom Learning Model Based on Task Exo Olo Using Story Articulate Media - Ali Umar Dani; Nur Fajriati (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the learning outcomes of students who are taught using the Flipped Classroom model based on Exo Olo Task with Articulate Storyline media. The design of this research is the Noneequivalent Control Group Design. sampling using a simple random sampling of 30 samples. The test instrument used is multiple choice questions. Conclusions were drawn based on the results of data processing and analysis using t-test and two-way ANOVA with SPSS 24.0. Based on the results of the analysis and discussion, in this study it was concluded that the Flipped Classroom learning model based on Exo Olo Task assisted by Articulate Storyline was effective compared to the Direct Instruction learning model.